Speed guidance model during the green phase based on a connected vehicle. (October 2016) - Wang, JF; Li, CC; Lv, JR; Yan, XD
Considering existing speed guidance models and their test method without reflecting upon the connected vehicle (CV) characteristics, a speed guidance model during the green phase is proposed using the real-time information of signal phase and timing, the vehicle travelling state, and environmental characteristics surrounding intersection. Considering the weakness of data non-synchronization and trajectory heterogeneity of the existing simulators, one-engine simulation architecture is introduced to validate the speed guidance model in the CV environment. The results indicate that the distribution of time headway shows a significant difference between with speed guidance and without speed guidance in the CV environment, and speed guidance can improve the harmonization of the time headway without degrading the travel efficiency. Speed guidance is affected by the space environment surrounding the intersection and V2I communication properties. Compared with a complicated space environment, for example an urban environment, speed guidance in a free space environment, for example a rural environment, has a better improvement of mobility and exhaust emission. In addition, the improvement of mobility and exhaust emission appears to have an increase tendency with the increase of transmission power and penetration rate.